-3x+69=x+189

Simple and best practice solution for -3x+69=x+189 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+69=x+189 equation:


Simplifying
-3x + 69 = x + 189

Reorder the terms:
69 + -3x = x + 189

Reorder the terms:
69 + -3x = 189 + x

Solving
69 + -3x = 189 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
69 + -3x + -1x = 189 + x + -1x

Combine like terms: -3x + -1x = -4x
69 + -4x = 189 + x + -1x

Combine like terms: x + -1x = 0
69 + -4x = 189 + 0
69 + -4x = 189

Add '-69' to each side of the equation.
69 + -69 + -4x = 189 + -69

Combine like terms: 69 + -69 = 0
0 + -4x = 189 + -69
-4x = 189 + -69

Combine like terms: 189 + -69 = 120
-4x = 120

Divide each side by '-4'.
x = -30

Simplifying
x = -30

See similar equations:

| 8(3a+6)=9(2a-2) | | 8.95m+.06=0m+.10 | | 6(y-9)=4(y-5) | | 2xsquared+5x+4=0 | | 7q+14=5(2q)-55 | | (16b-2)-5(3b+3)=-4 | | sqrt(8-x)+4-sqrt(4x-3)=0 | | (3x+2)(2x-1)=0 | | 10x-15=25-2x | | 5x+7=6+3x+1+2x | | ln(8-9x)=-1 | | ln(9x+8)=-1 | | -6q+72=q+269 | | 2(3+w)=41 | | 30x+5=125 | | 13p+3=p-597 | | x+(x+2)=108 | | 5(2x-4)=3(3x+6) | | (3(x-5a+9))= | | 5/3*2= | | x+12=4x-6 | | 20+1.25d=2.5d | | 5x-15x-7=5(4x+4) | | 8-n=1+2n-2n | | v+162=-4v-3 | | .04x+x=5200000 | | 117x^2+8xy+117y^2-484x-484y=12705 | | 6+x=26 | | b+84=-5b-6 | | -5-(15y-1)=2(7x-16)-x | | -4(-4+7x)=-152 | | 2x+2y+6=(x)(y)+3 |

Equations solver categories